Methodologically speaking: innovative approaches to knowledge and text in creative writing research. Issue 2 (4th May 2017) - Sempert, Mattie; Sawtell, Louise; Murray, Peta; Langley, Sophie; Batty, Craig
ABSTRACT: This article considers how creative writers use research to experiment with and expand the written form. Focussing on modes of storytelling for fiction and non-fiction, four current research degree candidates and a supervisor-mentor from RMIT University present snapshots of research works in progress, to reveal how they are negotiating the sticky yet rich relationship between theory and practice. Specifically, they offer innovative ways of expanding the written form to combine creative and critical modes of thought, resulting in distinctive contributions to knowledge and practice that are relevant to their genres, forms and subject matters. The candidates, who are working across the lyric essay, screenwriting, performance writing and radio, are also members of a peer-to-peer group facilitated by the supervisor-mentor, which over a four-year period has supported research training in creative writing and assisted in the formation of new research identities. This collaborative support structure has helped candidates to transform from creative writers to creative writing researchers, encouraging playfulness and experimentation yet underpinned by the needs of academic rigour. This article thus offers a collective, reflective approach to finding innovation in/through creative writing research – methodologically speaking.